Locality and many-body quantum spectra - Garratt, SJ (2021)
This thesis is concerned with many-body quantum dynamics in lattice models. Our focus is on the spectral properties of Floquet operators that describe local interactions in one dimension. Physical properties are expressed as multiple sums over paths in the many-body Fock space, and this leads naturally to interpretations in terms of interference effects, or of paired paths. By averaging properties over ensembles of random systems we wash out non-universal interference effects, and study the structures which survive.